Efectos de temperatura y tiempo de deshidratación, en características físicas y sensoriales de cebolla perla (Allium cepa L) en polvo - Nevárez Loor, Rosario Gissela (2016)
The goal of this research was to determine the effects of freezing temperature and dehydration time in the process of dehydrate-freezing, in the physical and sensory characteristics of pearl onion(Allium cepa L) powder. The experimental design applied was a factorial arrangement AxB with three replicates for every treatments, using as experimental unit 1 pound of pearl onion. The factors in studies were as follow. A: Freezing temperatures (-20, -40 y -60°C) and B: Dehydration time (8, 12 and 16 horas). The evaluated variables in all the treatments in this research were as follow: physical properties ( humidity and ashes), organoleptic analysis (smell, color and texture), while, the best treatment of this experimental research were evaluated the variables of mould and yeast. This way, it is concluded that the ideal time of dehydration-freezing for onion powder (Allium cepa) is eight hours. Using this time the process is reduced causing variations on the physical variables.